ANALISIS KESALAHAN PENGGUNAAN EJAAN DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) GURU SEKOLAH DASAR KECAMATAN ULUJADI - Lantuba, Yanis Men; Lembah, Gazali; Nur, Yunidar (BAHASANTODEA, 2017)
The research problems were (1) what form of spelling errors and punctuation in preparing the lesson plan for elementary school teachers in Ulujadi district?, (2) what the factors cause spelling errors Â and punctuation in preparing the lesson plan for elementary school teachers in Ulujadi district?. The objective of this research is to describe the form of spelling errors and punctuation and the factors that cause spelling errors and punctuation in preparing the lesson plan for elementary school teachers in Ulujadi district?. This research method was descriptive that explain and present accurate data about spelling errors and punctuation and to provide instructions according to the Indonesian language spelling rules. The data were collected through observation, documentation, and interviews. The results of the research show that the mistakes in the preparation of the lesson plan for elementary school teacher in Ulujadi district are the misuse of capital letters, misuse of small letters, misuse of words, and misuse of punctuation. The causes of spelling error in preparing the lesson plan for elementary school teacher in Ulujadi district are as follow: First, error is caused by a lack of understanding of language rules called competency factors. Second, there is a lack of supervision and correction from the principal about the lesson plan for the teacher. Third, there is a lack of training activities from the education department to elementary school teachers. Fourth, there is a guidebook of lesson plan for elementary school teacher. Fifth, writing is not a priority in preparing the lesson plan, the most important is the content of the lesson plan itself so that the teachers do not pay attention to the writing rules. To achieve spelling usage in preparing the lesson plan, commitment from all parties is needed to make improvements.